Impact of alcohol–diesel fuel blends on soot primary particle size in a compression ignition engine - Martos-Ramos, Francisco Javier; Doustar, O.; Zeraati-Rezaei, S; Herreros, J.M; Tsolakis, A. (Elsevier, 2022)
The use of alternative fuels, such as bio-alcohols, in advanced propulsion systems could a feasible strategy to address several of the current issues associated to the use of internal combustion engines fuelled by carbonaceous fossil fuels. Particularly, soot particles, are one of the key pollutants emitted from compression ignition engines. Therefore, the development of soot formation prediction models providing new understanding on the impact of alternative fuels combustion in compression ignition engines become essential for soot mitigation purposes. This study proposes a new semi-empirical model that predicts in-cylinder soot primary particle growth from an engine fuelled with alcohol–diesel fuel blends. The model uses macroscopic experimental measurements of engine parameters such as instantaneous in-cylinder pressure. Furthermore, an empirical correlation is presented predicting the mean soot primary particle size as a function of alcohol–diesel fuel blend properties and fuel/air ratio. The experimental measurement of primary soot particle mean size are obtained from High Resolution Transmission Electron Microscope (HT-TEM) micrographs obtained from soot particles collected via thermophoresis. Overall, the research findings presented in this work contributes to propose environmentally friendly fuel candidates for transportation.
Keywords: Carburantes; Motores de combustión interna -- Combustión; Ingeniería térmica; Primary particle diameter; Soot; Compression ignition engines; Semi-empirical modelling; Alcoholic fuel blends